The Effect Of Product Quality And Price On The Decision To Purchase Halal Cosmetics - Muchran, Muchriady; BL, Muchran (Advances in Social Sciences Research Journal, 2019)
Effect of product quality and price on purchasing decisions for Halal cosmetic products. The research location in Makassar (Indonesia) is Panrefukang Makassar Carrefour consumers. Respondents were taken randomly, 55 samples without looking at religious background. The study was conducted for two months, in May - 2019. This study aims to determine how the influence of product quality and wardah cosmetic product prices on consumer purchasing decisions. This cosmetic product has the power of halal brand image and also as a pioneer of halal cosmetics. Based on the results of data analysis, the results of the study indicate that the product quality variable (X1) and price variable (X2) have a positive and significant effect on purchasing decisions. Thus the halal brand image that is supported by product quality and affordable prices will convince consumers of Wardah’s cosmetics purchasing decisions.